Applying the concept of "number needed to treat" to the formulation of daily ambient air quality standards. (May 2019) - Ruan, Zengliang; Qian, Zhengmin (Min); Xu, Yanjun; Wu, Jun; Kan, Haidong; Yang, Yin; Acharya, Bipin Kumar; Jiang, Chengsheng; Syberg, Kevin M.; Iwelunmor, Juliet; Ma, Wenjun; Lin, Hualiang
Abstract: The World Health Organization sets up the Ambient Air Quality Guidelines mainly based on short-term and long-term health effects of air pollution. Previous studies, however, have generally revealed a non-threshold concentration-response relationship between air pollution and health, making it difficult to determine a concentration, below which no obvious health effects can be observed. Here we proposed a novel approach based on the concept of "number needed to treat", specifically, we calculated the reduction in air pollution concentrations needed to avoid one death corresponding to different hypothetical concentration standards; the one with the smallest value would be the most practical concentration standard. As an example, we applied this approach to the daily standard of ambient PM2.5 (particulate matter with aerodynamic diameter ≤2.5 μm) in four Chinese cities. The calculation was based on the association between daily mortality and ambient PM2.5, which was examined by a generalized additive model with adjustment of important covariates. Significant associations were observed between PM2.5 and mortality. Our analyses suggested that it is appropriate to have 50 μg/m 3 as the daily standard of ambient PM2.5 for the study area, compared to the current standard of which were directly adopted from the national standard of 75 μg/m 3 . This novel approach should be considered when planning and/or revising the ambient air quality guidelines/standards. Highlights: There is limited method for air pollution standard formulation. The "number needed to treat" was proposed as one potential method. We examined the acute association between PM2.5 and mortality in four Chinese cities. We then calculated the reduction in air pollution concentrations needed to avoid one death. Finally, we suggested that 50 μg/m 3 should be considered as daily standard of ambient PM2.5 in the study area. Abstract : Capsule: This study proposes a new "number needed to treat" approach to help establish or revise daily ambient air quality standards.